Nitrous oxide emission in a laboratory anoxic-oxic process at different influent pHs: Generation pathways and the composition and function of bacterial community. (May 2021) - Guo, Jingbo; Cong, Qiwei; Zhang, Jun; Zhang, Lanhe; Meng, Lingwei; Liu, Mingwei; Ma, Fang
Graphical abstract: Highlights: Incomplete oxidation in oxic tanks was the primary source of N2 O. N2 O in anoxic tank was mainly generated by nitrifier denitrification. No direct correlation existed between N2 O and nitrifiers/denitrifiers abundances. The impacts of pH relied on response of bacterial enzymes and nitrogen compounds. A pH optimum of 6–8 is recommended for nitrogen removal and N2 O mitigation. Abstract: This study focused on the nitrous oxide (N2 O) generation from the biological nitrogen removal process under different pH levels. To explore a pH optimum, the online N2 O emission and the bacterial composition and function in the anoxic–oxic process were investigated. The mean gaseous N2 O emission accounted for 0.329%, 0.103%, 0.085%, and 0.793% of the influent total nitrogen at pH of 5, 6, 8, and 9, respectively. Incomplete oxidation in oxic tanks was the primary source of N2 O, while N2 O in the anoxic tank was mainly generated by nitrifier denitrification. No direct correlations were observed between N2 O emission and potential nitrifiers and denitrifiers. The impacts of pH on N2 O generation were more likely related to the response of bacterial enzymes and nitrogen compounds, rather than the feedback of bacterial community structure itself. Above all, an influent pH range of 6–8 is recommended for nitrogen removal and N2 O mitigation in anoxic–oxic process.